The survivor [compact disc, unabridged] : a Mitch Rapp novel - Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2015)
Top secret data has been stolen from the CIA, and the only man who knows its hiding place is dead. CIA operative Mitch Rapp must race to find the classified information in this blistering novel that picks up where "The Last Man" left off in Vince Flynn's bestselling series.